DEVELOPMENT OF SPANISH MACKEREL ODENG PRODUCTS THROUGH THE TEACHING FACTORY OF RIAU PROVINCE FISHERIES VOCATIONAL SCHOOL: EVALUATION OF FOOD SAFETY AND STRATEGY - Sari, Evi Maya; Syukroni, Ikbal; Hidayati, Arlina; Sumartini, Sumartini; Arkham, Muhammad Nur; Suryono, Suryono (Politeknik Kelautan dan Perikanan Dumai, 2025)
The increasing demand for high-value fishery products necessitates the development of safe and quality-processed seafood to support economic growth and vocational education. This study aims to develop Spanish mackerel fish cake (odeng) through the Teaching Factory program at the Fisheries Vocational High School of Riau Province, focusing on evaluating food safety. The odeng product was designed and produced by students as an effort to enhance practical skills while meeting local market demands. Food safety analysis included the measurement of moisture and ash content, as well as the detection of hazardous substances such as borax and synthetic dyes (rhodamine B and methanil yellow), to ensure product quality. The results showed a moisture content of 23.13% and an ash content of 2.33%, which complies with fish processed product standards. Tests for hazardous substances were negative, indicating that the product is safe for consumption and meets national food safety standards. This study highlights the potential of vocational education-based production systems in generating value-added fishery products with assured quality and safety. Further development and optimization are recommended to improve self-life and consumer acceptance. These findings offer valuable insights for the integration of education and industry in sustainable fishery product innovation.